A MARKOV CHAIN MODEL FOR ISLAMIC MICRO-FINANCING - Djaffar Lessy; Fouad Khoudjeti; Marc Diener; Francine Diener (Bank Indonesia, 2019)
This paper introduces a Markov chain model for Islamic micro-financing, especially mudarabah and murababah contract. Mudarabah and murabahah are two Islamic micro-financing contracts that have enormous potential in creating a balance between the monetary and sharia sector because these two products are moving to manage the business sector which undoubtedly adds value to the economic movement directly. On the other hand, these two contracts have the potential to cause problems in their implementation. The most common problem of the two contracts is asymmetric information, which consists of adverse selection and moral hazard. We propose the Markov chain model as a solution for the Islamic banks to reduce the risk because of adverse selection and moral hazard in mudarabah and murabahah contract. In our model, we also propose a mechanism to avoid strategic default in mudarabah contract. We observed two different probabilities of an applicant to become a beneficiary to find the solution to the problems. The results of this study, the bank can decrease the probability of an applicant to become a beneficiary to reduce the adverse selection and moral hazard in mudarabah and murabahah contract.